ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DI KOPERASI - Farabi, Ferro Al; Saebani, Akhmad (APSSAI ACCOUNTING REVIEW, 2022)
This study aims to determine the effect of technology Advancement, work experience, education, and training on the effectiveness of accounting information systems. The population of this research is the management of the Savings and Loans Cooperative of the Sub-Department of Food Security, Maritime Affairs, and Agriculture of the City of Adm. South Jakarta. This research uses purposive sampling technique and obtains 50 savings and loan cooperative administrators as respondents, this type of research is quantitative research. The research data were analyzed using multiple linear regression method using a significance level of 5% (0.05). The results of this study indicate that work experience and training have an influence on the effectiveness of accounting information systems, while technology Advancement and education have no effect on the effectiveness of accounting information systems.